2020
DOI: 10.1016/j.waojou.2020.100465
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Google Trends terms reporting allergies and the grass pollen season in Ukraine

Abstract: Background: Grass pollen allergy is an important trigger for the development of respiratory disorders. Defining the grass pollen season onset is critical for correct allergy diagnosis and personalized therapy. The development of a pan-European sentinel network for allergic diseases has raised the problem of translating the Google search terms into different European languages as well as defining specific pollen season characteristics in different regions. Grass pollen allergy was investigated due to high aller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
(43 reference statements)
0
1
0
3
Order By: Relevance
“…Previous studies have shown that web search analyses can help to predict medically relevant seasons or to identify unmet needs of patients. For example, web searches correlated with the pollen season or the occurrence of certain infectious diseases 19–21 . Thus, the aim of this study was to analyze AD‐related online search behavior in Germany as a whole and in 16 German cities, focusing on seasonal trends, meteorological influences, and geographic differences to identify on a population‐based level potential environmental trigger factors and unmet needs to optimize treatment options and allocation of healthcare resources.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that web search analyses can help to predict medically relevant seasons or to identify unmet needs of patients. For example, web searches correlated with the pollen season or the occurrence of certain infectious diseases 19–21 . Thus, the aim of this study was to analyze AD‐related online search behavior in Germany as a whole and in 16 German cities, focusing on seasonal trends, meteorological influences, and geographic differences to identify on a population‐based level potential environmental trigger factors and unmet needs to optimize treatment options and allocation of healthcare resources.…”
Section: Introductionmentioning
confidence: 99%
“…У якості зручного інструменту інфодеміології протягом тривалого часу активно використовується ресурс Google Trends [11,12,13], зокрема і для дослідження алергічних [15,16,17,18] та інфекційних хвороб [19,20].…”
Section: вступunclassified
“…Окремої уваги заслуговують можливості Google Trends як інструмента досліджень алергічних хвороб [15]. Попередніми нашими дослідженнями виявлені кириличні відповідники для прогнозування сезонів алергії на пилок трав, амброзію та альтернарію в Україні [28,29,30].…”
Section: обговоренняunclassified
“…Комбінація ключових слів пошукових запитів Google ККС була обрана, керуючись наступним: на початкових етапах дослідження термін «COVID-19» не набув ще широкого вжитку у населення України [9], а також вивчення кириличних відповідників пошукових запитів Google дозволяє надійно прогнозувати розвиток хвороб у загальнонаціональному масштабі [15,16].…”
Section: рис 4 -експоненціальна прогностична модель запитів модель Gт...unclassified